A rapid and sensitive analytical methodology for the simultaneous biomonitoring of two direct oral anticoagulant drugs and their major metabolites in thromboembolic disordered patients samples for clinical evaluations - Prakasham K.; Pan T.-Y.; Tan C.-H.; Wu C.-F.; Chandra P.; Cheng C.-M.; Chen W.; Tsai W.-C.; Ponnusamy V.K.; Wu M.-T. (My University, 2025)
Apixaban and dabigatran are the two major direct oral anticoagulant drugs to treat thromboembolic disordered patients. Increasing the clinical application for the thromboembolic disorder and monitoring the concentrations of apixaban, dabigatran, and their metabolites are essential in most clinical circumstances. In this work, we developed a rapid analytical methodology comprising of vortex-assisted salt-enhanced liquid-liquid microextraction technique coupled with UHPLC-MS/MS for the extraction and simultaneous determination of two major direct oral anticoagulant drugs (apixaban, dabigatran), and their two major metabolites from plasma, serum, and urine samples of patients. The developed method was optimized with various procedural steps and validated to study the analytical merits. The developed method yielded a good detection limit of 0.01 ∼ 0.37 ng/mL, 0.01 ∼ 0.32 ng/ml, and 0.01 ∼ 0.27 ng/mL for four target analytes in the plasma, serum, and urine matrices. Moreover, extraction recoveries ranged from 85.11 – 113.57% (for plasma), 89.63 – 110.47% (for serum), and 87.44 –106.79% (for urine samples) with 8.78% RSD. In addition, the method exhibited good R2 values of 0.999 for all four target analytes, and the specificity and carryover study revealed no carryover effect from the UHPLC-MS/MS system for determining the apixaban, dabigatran, and their metabolites. Due to the above advantages, the developed analytical technique was applied to examine 11 real-time clinical patients’ samples, and the observed results were satisfactory for all three different sample matrices. Therefore, this analytical method can be applied for biomonitoring apixaban, dabigatran, and their two major metabolites with high sensitivity in a short time for various clinical applications. © 2024 Elsevier B.V.